ENT300 LCH Box / Andrea Umang Ak Rahnie... [ et.al] - Rahnie, Andrea Umang; Datu Hassan, Dg Norfarini; Sarmon, Suryanie; Jafry, Edith Edna (2015)
Our business name is LCH Box. The business has been decided on the form of partnership, which consists of four partners in the team. The management team is headed by four experienced and professional level workers that will handle the management and operation of this company in order to get the best quality of product or services and maximum profit. All partners are encourage and entitled to participate in all business management. We agreed that Andrea Umang Ak Rahnie is our General Manager and Administration Manager, Suryanie Binti Sarmon is the Operational Manager, Edith Edna Jafry as Financial manager and Dg Norfarini Binti Datu Hassan as Marketing Manager. The selection of Manager is based on consensus among all the partners and selected based on the experience, skills and ability. Our main business activity, LCH Box is a company that provide lunch box or take away and dine in meals to the customers in area of Damansara. We do provide lunch box or take away and dine in or the customers that rather have their lunch at our restaurant. We also provide delivering services. In our business, we also operate the place for the customer to have their beverages and at the same time they wait for their clothes. The restaurant is located at 56, Jalan SS 21/1A, DamansaraUtama, 47400, Petaling Jaya, Selangor, Malaysia. This business premise is for both administrative building and restaurant. The company will start to operate on 7 February 2016.